Chemical and Biological Activities of Some Scorzonera Species: An In Vitro Study - Erden, Yavuz; Kırbağ, Sevda (Springer, 2015)
The present study was carried out on the phytochemical composition (total flavonoids and total polyphenols), antioxidant activity and antimicrobial effect of the Scorzonera suberosa (C. Koch), Scorzoneralatifolia (Fisch. and Mey.) and Scorzonera laciniata (L.). Total flavonoid and polyphenol contents of the species were determined using spectrophotometric methods. Effect of scavenging ABTS and DPPH free radical of species was compared with that of butylated hydroxytoluene. The antimicrobial effect of plant extracts was determined by the method of agar well diffusion. Additionally, after the oxidative stress induced by hydrogen peroxide, the effect of plant extracts on lipid peroxidation, protein and glutathione levels was determined in the yeast culture. As the result, plant extracts showed high antioxidant and antiradical effects. All plant samples had more pronounced antimicrobial effect on Escherichia coli and Bacillus megaterium. In addition, these samples showed antitoxic property and protective effect of cell viability in the probiotic yeast culture. © 2013, The National Academy of Sciences, India.
Keywords: Antioxidant capacity; Free radicals; Oxidative stress; Phytochemical composition; Scorzonera species; Yeast culture